Møder, relationer, populærkultur og repræsentation: Samtale med Tue Biering ved Solveig Gade - Gade, Solveig (Peripeti, 2022)
Møder, relationer, populærkultur og repræsentation. Interview with Bering by Gade. In this conversation, Gade draws a portrait of FIX&FOXY’s practices, and identifies some fundamental themes in contemporary theatre.